Between social control and citizen participation: political culture and health legitimacy - Mario Angelo Cenedesi Junior; Juliana Rei de Alcântara; Cláudio Eduardo Sousa Lima; Bárbara Thaisi Zago; Juliana Aparecida Pereira Ribeiro; Wendel Expedito Batista Martins (Aposta: Revista de Ciencias Sociales, 2026)
This study examines how Brazil, mainland China, and Taiwan construct health legitimacy through state capacity, political culture, and citizen participation. Using comparative political sociology and historical institutionalism, it identifies distinct pathways: Brazil emphasizes universal rights, China prioritizes state performance and stability, and Taiwan combines efficiency and technological governance. Health legitimacy reflects historically specific state–society configurations.